Tracking the New Trends in Immersive Virtual Reality-Assisted Foreign Language Education: A Systematic Review of Empirical Studies - Jianli Shi; Jirarat Sitthiworachart; Thanin Ratanaolarn (My University, 2023)
This article follows up on a previous review of 30 empirical studies that examined the use of immersive virtual reality (iVR) for teaching foreign language (FL) published before 2021. That review concluded that iVR was an emerging technology in FL education. However, since then, iVR technology has rapidly developed and garnered more attention in FL education. To track the new trends in iVR-assisted FL education, we conducted a follow-up systematic review using the PRISMA method. We found 38 empirical studies published between January 2021 and March 2023, which is more than those previously found. Our findings revealed new trends and more benefits, yet more challenges compared to the previous review. The new trends discovered include an increase in both the quantity and quality of publications, research expanding from adults to younger learners, and a variety of language skills investigated. Moreover, the research focus has broadened from the iVR technology per se to its influence on different learners (e.g., gender and FL level) and the combination with other technologies or instructional strategies, such as High-iVR (i.e., users can interact with the virtual environment naturally with a sense of physical presence and full-body movement) and learner-created VR environments. The reported benefits of iVR-assisted FL education include enhancing learners’ engagement and FL skills, while the challenges include handling operational issues and unstable internet connection. Drawing from the insights gathered through this review, we derive educational, technological, and research implications that contribute to the field of iVR-assisted FL education.
Keywords: Tracking (education); Empirical Research; Virtual Reality Applications and Impacts